Technical Note: Is there a role for external technical support in the Community-Led Total Sanitation (CLTS) approach? - Papafilippou, Nikolaos; Templeton, Michael R.; Ali, Mansoor (International Development Planning Review, 2011)
Community-Led Total Sanitation (CLTS) involves creating community health awareness, changing behaviours, generating a demand for sanitation, and finally the design and construction of sanitation solutions (e.g. latrines). The CLTS approach intentionally avoids any up-front external subsidies or technical support throughout the process. By excluding technical support, the CLTS philosophy argues that people innovate and develop a sense of ownership for the latrines that they build, which in turn leads to sustainable use of the latrines. This article questions this exclusion of technical support. Specifically, the article summarises the CLTS approach, identifies innovative designs that have been implemented by CLTS communities, discusses the technical weaknesses of some of these designs, and reports the responses from a survey of leading sanitation experts and practitioners regarding the potential need for technical support in CLTS. The study findings suggest that community innovations resulting from CLTS are not always satisfactory in terms of hygiene and quality of physical construction and may impede the pathway to sustainable improved sanitation. The article also suggests how and when technical support may be included in the CLTS process, without compromising the core principles of the approach.